2022
DOI: 10.3389/fvets.2022.986619
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of SARS-CoV-2 in companion animals in China

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) can be transmitted from human to companion animals. The national wide serological surveillance against SARS-CoV-2 was conducted among pet animals, mainly in cats and dogs, 1 year after the first outbreak of COVID-19 in China. All sera were tested for SARS-CoV-2 IgG antibodies using an indirect enzyme linked immunosorbent assay (ELISA) based on the receptor binding domain (RBD) of spike protein. This late survey takes advantage of the short duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…In summary, our data confirmed that cats and dogs in close contact with people can develop an antibody response against SARS-CoV-2 infection, and similar to other studies, the seroprevalence of SARS-CoV-2 among cats and dogs belonging to owners of unknown COVID-19 status was low [ 28 , 29 , 30 , 31 , 32 ]. This study also highlights the need to establish species-specific serological assays that can assess neutralizing antibodies in companion animals to provide accurate measurements of active infection in households and communities to ensure that all transmission opportunities are prevented.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In summary, our data confirmed that cats and dogs in close contact with people can develop an antibody response against SARS-CoV-2 infection, and similar to other studies, the seroprevalence of SARS-CoV-2 among cats and dogs belonging to owners of unknown COVID-19 status was low [ 28 , 29 , 30 , 31 , 32 ]. This study also highlights the need to establish species-specific serological assays that can assess neutralizing antibodies in companion animals to provide accurate measurements of active infection in households and communities to ensure that all transmission opportunities are prevented.…”
Section: Discussionsupporting
confidence: 91%
“…Natural SARS-CoV-2 infection has been sporadically detected in companion animals, with human-to-animal transmission suspected in almost all cases [ 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Serological surveillance of cats and dogs has been conducted in different countries since the early phases of the COVID-19 pandemic [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Specifically, the seroprevalence of SARS-CoV-2 in cats with an unknown history of exposure to the virus was found to be 0.015% (2/13397) in China [ 28 ], 0.69% (6/920) in Germany [ 29 ], 0.76% (1/131) in Croatia [ 30 ], 0.4% (2/500) in the Netherlands [ 31 ], 3.3% (15/451) in Italy [ 32 ], 18.9% (46/243) in Poland [ 33 ] and 7.3% (40/547) in Brazil [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations